An Efficient and Lightweight Deniably Authenticated Encryption Scheme for e-Mail Security - Jayaprakash Kar (IEEE Access, 2019)
The most important security requirements to secure electronic mail (e-mail) systems are: confidentiality, authentication, non-repudiation and data integrity. In conventional e-mail systems, Secure/Multipurpose Internet Mail Extensions (S/MIME) and Pretty Good Privacy (PGP) digital envelops are used to satisfy these security requirements. However, confidentiality and authentication are performed in two different phases, which increases computations and leads to more energy consumption. Moreover, the receiver can easily reveal the source of the message, violating the sender's privacy. In this paper, we propose a low-cost deniably authenticated encryption scheme (DA-ENS), where all the cryptographic primitives are being performed in a single logical step to achieve these goals. Experimental results show that our scheme, DA-ENS, achieves low computational cost and communication overhead at 80-bit, 112-bit, 128-bit, 192-bit and 256-bit security levels. Energy consumption is shown to be reduced to 80%, 67%, 42%, 62% and 48% compared to similar schemes SL+BF, LXJ+BF, Fagen Li et al. (FL), AJL and CZJZJSZ respectively. Also, we have proven that, our scheme DA-ENS is provably secure in random oracle model.